Morphological and phylogenetic features of the Crimean population of Juniperus deltoids R.P. Adams - A. O. Lantushenko; O. O. Korenkova; A. A. Syrovets; Ya. V. Meger; P. A. Korenkov; O. M. Shevchuk (Вавиловский журнал генетики и селекции)
Juniperus deltoides is a relict species from the Tertiary Period. It is a typical representative of the Mediterranean group of the section Juniperus. It is included in the Red Books of the Republic of Crimea and the city of Sevastopol. Until recently, it was believed that a population of J. oxycedrus grew in Crimea. Currently, J. deltoides is described as a cryptic species, morphologically difficult to distinguish from J. oxycedrus. As a result, it became necessary to conduct a series of detailed studies to determine the morphological and phylogenetic features of the Crimean cryptic population in order to identify it as being one of the species of the cryptic pair. The studies were carried out in two stages: at the first stage, the morphological features of the vegetative and generative organs and their difference from J. oxycedrus were determined; the second stage included genetic research. The length of the needles of the Crimean population is 12.94 ± 0.19 mm, which corresponds to the Eastern Italian population of J. deltoides. At the same time, the width of the needles is 1.39 ± 0.02 mm, which is typical of the Portuguese population of J. oxycedrus. The dimensions of the cones are d1 (conditional height) = 7.54 ± 0.14 mm, and d2 (conditional width) = 9.11 ± 0.09 mm, which is more in line with J. deltoides. The shapes of the cones are very diverse. Some individuals have cones, the covering scales of which are visually indistinguishable, and their tops are completely fused. A similar phenomenon is characteristic of the Western Mediterranean populations of J. oxycedrus. Morphological analysis of the vegetative and generative organs of J. deltoides showed that when these two traits are combined, it is not possible to reliably distinguish between J. deltoides and J. oxycedrus individuals. Nuclear (ITS internal transcribed spacer) and chloroplast (petN-psbM, trnS-trnG) non-coding regions of the genome were used for genetic analysis. Studies have shown that the nuclear regions of genes have greater variability than chloroplast regions. The sequences obtained in this work formed a clade with J. deltoides samples 9430 and 9431 (BAYLU) growing in Turkey, which makes it possible to assign the samples studied to J. deltoides.